Biocontrol efficacy of apigenin isolated from Anisomeles indica (L.) Kuntze against immature stages of Culex quinquefasciatus (Say, 1823) and its in silico studies. (March 2023) - Samuel, Rajan; Pathalam, Ganesan; Babu, Velmurugan; Kamaraj, Ragavendran; Subramanian, Mutheeswaran; Antony, Stalin; Sanmugapriya, Nagul Kumar; Palaniswamy, Senthilkumaar; Savarimuthu, Ignacimuthu
Abstract: Culex quinquefasciatus is a vector of medical importance since it transmits pathogens to humans, and domestic and wild animals. Synthetic chemical insecticides which are widely used to control mosquitoes are also reported to cause severe threats to humans, non-target organisms and the environment. However, bioactive products derived from plants for mosquito control are eco-friendly, target-specific, safe to non-target organisms, biodegradable, less toxic and reduce development of drug resistance. Therefore, the goal of the present study was to evaluate the biocontrol efficacy of Anisomeles indica (L.) Kuntze on immature stages namely eggs, pupae, and larvae of Cx. quinquefasciatus . In the preliminary screening, hexane and chloroform extracts were found active which were blended and subjected to column chromatography that finally yielded the active phytochemical apigenin. Against Cx. quinquefasciatus, apigenin caused 74% egg mortality at 2 ppm concentration after 120 h of exposure, 72% larvicidal activity with LC50 and LC90 values of 1.3 and 3.9 ppm, respectively, after 24 h, and 65% pupicidal activity with LC50 and LC90 values of 1.3 and 3.7 ppm, respectively, after 24 h exposure. Histopathology study of the exposed larvae revealed that apigenin caused damages on the midgut epithelial columnar cells and remarkable deformities in their structural development, whereas no toxicity was caused on the tested non-target organisms, Gambusia affinis (mosquito fish) and Diplonychus indicus (water bug). Docking study demonstrated that apigenin bounded and inhibited AChE1 of Cx. quinquefasciatus, which resulted in larval mortality. The present study manifested that the isolated metabolite apigenin from A. indica could be a promising biopesticide to control vector mosquitoes. Highlights: Different tribes and villagers traditionally use Anisomeles indica (L.) Kuntze to combat mosquito annoyance. Hexane-chloroform extract of A. indica exhibited remarkable control efficacy against immature stages of Cx. quinquefasciatus. Apigenin caused significant damages in the midgut and inhibited growth in the larvae of Cx. quinquefasciatus. Apigenin bounded and inhibited acetylcholinesterase (AChE1) of Cx. quinquefasciatus that resulted in larval mortality. Apigenin induced no effect on the tested non-target organisms G. affinis and D. indicus.